Localization of the PsbH subunit in photosystem II from the Synechocystis 6803 using the His-tagged Ni-NTA Nanogold labeling - Bumba, Ladislav; Tichý, Martin; Dobáková, Marika; Komenda, Josef; Vácha, F (Journal of structural biology, 2005)
The PsbH protein belongs to a group of small protein subunits of photosystem II (PSII) complex. This protein is predicted to have a single transmembrane helix and it is important for the assembly of the PSII complex as well as for the proper function at the acceptor side of PSII. To identify the location of the PsbH subunit, the PSII complex with His-tagged PsbH protein was isolated from the cyanobacterium Synechocystis sp. PCC 6803 and labeled by Ni(2+)-nitrilo triacetic acid Nanogold. Electron microscopy followed by single particle image analysis identified the location of the labeled His-tagged PsbH protein at the periphery of the dimeric PSII complex. These results indicate that the N terminus of the PsbH protein is located at the stromal surface of the PSII complex and close to the CP47 protein.
Keywords: financování organizované; Nitrilotriacetic Acid; kyselina nitrilotrioctová; Synechocystis; fosfoproteiny; nikl; Protein Structure, Quaternary; bakteriální proteiny; podjednotky proteinů; Thylakoids; Bacterial Proteins; Immunohistochemistry; Phosphoproteins; tylakoidy; Photosystem II Protein Complex; imunohistochemie; fotosystém II (proteinový komplex); Financing, Organized; Macromolecular Substances; Protein Subunits; Nickel; makromolekulární látky; kvarterní struktura proteinů